2006
DOI: 10.1158/1055-9965.epi-05-0614
|View full text |Cite
|
Sign up to set email alerts
|

Meat Consumption among Black and White Men and Risk of Prostate Cancer in the Cancer Prevention Study II Nutrition Cohort

Abstract: Previous epidemiologic studies have suggested that intake of red meat may be associated with increased risk of prostate cancer. Few studies, however, have examined these associations by race. We examined intake of red meat, processed meat, and poultry in relation to incident prostate cancer among Black and White men in the Cancer Prevention Study II Nutrition Cohort. Participants in the study completed a detailed questionnaire on diet, medical history, and lifestyle in 1992 to 1993. After excluding men with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
93
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 33 publications
4
93
1
Order By: Relevance
“…[23][24][25][26][27] Given that family history reflects not only shared genes but also shared environments and common behaviors, 14 lower risk estimates could in part result from less variability in the latter factors, particularly in a relatively homogeneous population such as in the present study. In this regard, it is interesting to note that having a family history of other cancers that do share some of the same risk factors with prostate cancer (i.e., red meat consumption with colorectal cancer) 28,29 was not associated with prostate cancer risk in our study, although 1 study reported that family history of breast cancer was associated with a prostate cancer relative risk of 1.7. 30 Although it has been thought that 5-10% of prostate cancer is accounted for by genetic susceptibility, 31 an analysis of monozygotic and dizygotic twin pairs in Scandinavia concluded that 42% (95% CI, 29-50%) of prostate cancer risk may be heritable.…”
Section: Discussioncontrasting
confidence: 44%
“…[23][24][25][26][27] Given that family history reflects not only shared genes but also shared environments and common behaviors, 14 lower risk estimates could in part result from less variability in the latter factors, particularly in a relatively homogeneous population such as in the present study. In this regard, it is interesting to note that having a family history of other cancers that do share some of the same risk factors with prostate cancer (i.e., red meat consumption with colorectal cancer) 28,29 was not associated with prostate cancer risk in our study, although 1 study reported that family history of breast cancer was associated with a prostate cancer relative risk of 1.7. 30 Although it has been thought that 5-10% of prostate cancer is accounted for by genetic susceptibility, 31 an analysis of monozygotic and dizygotic twin pairs in Scandinavia concluded that 42% (95% CI, 29-50%) of prostate cancer risk may be heritable.…”
Section: Discussioncontrasting
confidence: 44%
“…The Cancer Prevention Study II reported an increased risk with higher intake of total red meat among Black men (RR of highest vs. lowest quartile 5 2.0, 95% CI 5 1.0-4.2), but not among White men. 33 One populationbased case-control study also observed that increased intake of foods high in animal fat was associated with prostate cancer among American blacks, but not among American whites. 27 However, we did not find a stronger relationship between meat intake and risk in African Americans than in Whites in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…7,[21][22][23][24] For meat intake, the findings have also been mixed. [5][6][7]9,10,[25][26][27][28][29][30][31][32][33] To further explore these relationships, we examined the association between prostate cancer risk and the intake of fat (including total, saturated, monounsaturated and polyunsaturated fat, and n-3 and n-6 fatty acids), cholesterol, meat (including total, red, processed and poultry), fish and fats from meat in the Multiethnic Cohort Study. …”
mentioning
confidence: 99%
“…Overall, epidemiologic evidence for consumption of meat as a risk factor for prostate cancer risk is equivocal (11). In two of the more recent studies of prostate cancer and meat consumption conducted in the United States, increased meat consumption was positively associated with prostate cancer risk in African Americans, but not Caucasians (12,13). In the United States, African-American men have a 60% higher incidence of prostate cancer compared with whites (14).…”
Section: Introductionmentioning
confidence: 99%